Detection of HIV-1 p24 antigen using a simple and highly sensitive chemiluminescence immunoassay. (July 2013) - Zhao, Pengxiang; Feng, Juan; Wu, Yanan; Xu, Fei; Lv, Chuanchen; Fu, Emily; Ma, Xuemei; Zeng, Yi
Aim: Our study aimed to improve the p24 antigen assay, which is a well-established and widely adopted method for the early detection of HIV-1 infections, in order to increase its sensitivity and efficiency and reduce its cost if possible.Materials & methods: We tested HIV-1 standard p24-positive samples and an HIV-1 p24 antigen panel using a new luminol-based chemiluminescence immunoassay (CLIA) based on a typical 'sandwich' p24 ELISA with two antibodies, but utilizing luminol as the luminescence compound, which is oxidized by hydrogen peroxide in the presence of horseradish peroxidase in an alkaline environment. A standard curve for the p24 antigen CLIA was generated and fitted a third-order polynomial regression model very well. To quantify p24 antigen, we investigated the linear standard curve fitting by measuring and comparing the effective assay range, r 2 value and error of each function.Results: The p24 antigen CLIA showed a detection limit of 0.5 pg/ml and a detection range of 0.5–5 × 10 3 pg/ml. The specificity and sensitivity of this assay were further evaluated, and were both found to be 100% for the HIV-1 p24 antigen panel. The luminescence reaction of the CLIA p24 assay takes only 2 min to perform, which greatly reduced the diagnosis time. Additionally, the CLIA p24 assay is as affordable as the normal ELISA method.Conclusion: In our studies, the p24 antigen CLIA shows improved sensitivity, a wider range of response and was less time-consuming than ELISA, as traditional ELISA uses chromogen or a substrate that changes color when cleaved by the enzyme attached to a second antibody. This seems to be an easy and affordable method for the diagnosis of HIV-1 infection and monitoring of disease progression in developing countries. Although more advantages have been seen in CLIA than in ELISA, additional studies are still needed to confirm this.